PENGARUH KEBIJAKAN DEVIDEN TERHADAP NILAI PERUSAHAAN PROPERTI YANG TERDAFTAR DI BURSA EFEK INDONESIA (PERIODE 2016-2018) - Marcela Pertiwi (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2020)
In accordance with the formulation of the problem stated above, the purpose of this study is obtain concrete (empirical) evidence in the form of data and fact about the effect of dividend policy on the value pf companies listed on the stock exchange in the 2016-2018 period. Data collection in this study was carried out with applied research technique, the population in this study are all manufacturing companies sub-sector property and real estate, amounting to 48 companies, so as a sample the researchers took 21 companies. Research result of t-test calculations have significant effect betwen dividend policy on firm value. This means that the size of the dividend value will effect the stock prices of manufacturing companies in 2016- 2018 period. Contibution of divident police to the value of the company where the value of the dividend contributed to the value of the company. The greater the size of the company, the greater of the quantity of the dividend policy prepared by the company so that it contributes to the value of the company.